Approach learning high-order thinking skills to improve civic knowledge in Pancasila and Civic Education - Biringan, Julien; Limeranto, Rylien Felicia; Sample, Ferry Lourens Korompis (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
Higher-order thinking skills require students to process information critically using specific methods to develop new understandings and insights. This approach encourages students to integrate reality with critical thinking, allowing them to analyse, synthesise, conclude, and evaluate information before reaching a final decision. This study employs an explanatory subjective exploration approach, focusing on interactive processes that provide a comprehensive description through subjective analysis. Educators formulate questions based on specific learning indicators, using simple and accessible language to ensure students can engage effectively. Classroom debates help students develop fundamental thinking skills, enabling them to analyse and address issues objectively without bias. In Pancasila and Civic Education (PCE), the HOTS (Higher Order Thinking Skills) approach is applied selectively, as students have varying capacities. Teachers assess students through written responses to comprehension-based questions derived from lesson materials. Indonesia's education system emphasises civic education, aiming to enhance students' understanding of national identity and uniqueness.